Dynamics And Enforcement Of Election Legal Issues In Lampung Province - Santoso, Rudi; Maimun, Maimun (DE LEGA LATA: JURNAL ILMU HUKUM, 2024)
This research is to reveal the dynamics and problems of holding elections in 2019. Because, in the simultaneous elections there were many violations and solutions need to be found for the sake of better future elections. The research uses library and field methods. The data was obtained from books, statutory regulations and scientific articles. Meanwhile, field research was obtained from the general Election Supervisory Agency (Bawaslu), Lampung Province. This research concludes that the 2019 election has various dynamics and problems. In terms of violations, there are administrative violations to election crimes. Meanwhile, the problems faced are the difficulty of coordinating with the Integrated Law Enforcement (Gakumdu) Center, lack of human resources and minimal budget as well as inadequate facilities and infrastructure. Solutions to these problems must be found in order to hold future elections better than before